Secondary inorganic aerosol during heating season in a megacity in Northeast China: Evidence for heterogeneous chemistry in severe cold climate region. (December 2020) - Cheng, Yuan; Yu, Qin-qin; Liu, Jiu-meng; Du, Zhen-yu; Liang, Lin-lin; Geng, Guan-nan; Ma, Wan-li; Qi, Hong; Zhang, Qiang; He, Ke-bin
Abstract: The characteristics of secondary inorganic aerosol including sulfate, nitrate and ammonium (SNA) were investigated during a six-month long heating season in the Harbin-Changchun metropolitan area, i.e., China's only national-level city cluster located in the severe cold climate region. The contribution of SNA to fine particulate matter (PM2.5 ) tended to decrease with increasing PM2.5 concentration, opposite to the trend repeatedly observed during winter in Beijing. Heterogeneous sulfate formation was still evident when the daily average temperature was as low as below −10 °C, with the preconditions of high relative humidity (RH; above ∼80%) and high nitrogen dioxide (above ∼60 μg/m 3 ). Both the sulfur oxidation ratio (SOR) and nitrogen oxidation ratio (NOR) were enhanced at high RH, reaching ∼0.3. However, the high RH conditions were not commonly seen during the heating season, which should be responsible for the overall lack of linkage between the SNA contribution and PM2.5 temporal variation. Graphical abstract: Image 1 Highlights: SNA was investigated during a six-month long heating season in Harbin. Sulfate/PM2.5 ratio decreased with increasing PM2.5, opposite to Beijing's winter. Heterogeneous sulfate formation was evident despite low ambient temperatures. Preconditions for heterogeneous sulfate formation included high RH and high NO2 . Nitrate and SOA were also enhanced under high RH conditions.